LIFE QUALITY EVALUATION IN ADULT WOMEN WITH FIBROMIALGY DIAGNOSIS (Fiep Bulletin - online, 2015)
Fibromialgy is a form of rheumatism that attacks woven soft of the body causing pain, to dilate, fatigues, contraction muscle, to shorten muscle, besides psychological upset as depression, anxiety and hopelessness; attacking the feminine sex predominantly. The diffuse pain and chronic cause also disturbances of the sleep, headache tensional and nervousness; being able to the patient to develop, tendencies to the isolation and seclusion, because the pain disables of relating socially; causing, important limitations in the life quality. OBJECTIVE: To evaluate the quality of adult women's life with fibromialgy diagnosis.  METHODS: They were used, questionnaire of evaluation of the life quality - Whoqol - Bref, version abbreviated in Portuguese, the Inventories of Beck (Depression, Anxiety and hopelessness); and scale of pain of Borg (CR10). The sample was composed by twenty subjects female, with clinical diagnosis of fibromialgy, which were submitted to the treatment physiotherapy (Ultrasound, TENS, Cinesioterapy). The data were obtained in two moments, being before the treatment and after twenty complete sessions, analyzed through descriptive analysis and test of Wilcoxon. RESULTS: The found results drive us to assure that the women with Syndrome of Fibromialgy presented in the first moment, pré-treatment, alterations in the life quality in the negative sense, high levels of pain; psychological aspects in negative levels. The physical agents' use as Ultrasound, you Have and Cinesioterapy, were proposed in the sense of interfering in those conditions, in this sense there were changes in the positive sense of those alterations after the accomplishment of the treatment. CONCLUSION: Analyzing the results, it can be observed that there was increase in the positive sense of the quality of life of the patients bearers of Fibromialgy, after the accomplishment of the sessions physiotherapy, when verified through the questionnaire Whoqol - Bref.
Keywords: Life quality; Fibromialgy; Treatment physiotherapy